(untitled) (Research, Society and Development, 2022)
Sustainable development refers to agricultural and industrial activities and the understanding of sustainability assumes greater complexity, which requires economic, social, environmental, institutional, technological, cultural and geographical emphasis to be considered, because what is sustainable for one region may not be for another. The article aims to show methodological criteria for the construction of the Global Sustainability Index (GSI) and its importance in the evaluation of public policies of sustainable milk production in contemporary times. The methodology considers the economic, social, environmental, institutional and technological dimensions, for better assessing the sustainable of economically active activities. The survey took place in Rondônia with 400 dairy farmers, where we obtained the GSI that achieved average sustainability, GSI = 0.42. The economic dimension presented an index of 0.52, being the most sustainable among the analyzed dimensions. Following the decreasing order, comes the social and environmental, with average sustainability of 0.44 and 0.41, and, with low sustainability, was the technological dimension, which showed an index of 0.39, and, the institutional with 0.32 decimal points of sustainability. This result indicates the need for political and technological efforts for better performance in the sector.